2014
DOI: 10.1007/s00339-014-8724-5
|View full text |Cite
|
Sign up to set email alerts
|

Resistive high-impedance surfaces (RHIS) as absorbers for oblique incidence electromagnetic waves

Abstract: Resistive highimpedance surfaces (RHIS) as absorbers for oblique incidence electromagnetic waves. Applied physics.Abstract This paper presents a lightweight microwave absorber suitable for space applications. The absorber is based on a resistive high-impedance surface (RHIS) optimized to achieve reflection under -15 dB in the band (2-2.3 GHz) at oblique incidence for transverse electric (TE) and transverse magnetic (TM) polarizations. A first classical isotropic RHIS structure is shown to be limited to angles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…The optimal resistor value depends on both angle of incidence and wave polarization w = 9.7 mm g=0.25 mm h = 2.36 mm r = 2. [15]. This structure is characterized by the absorption band that we defined by |U| \ -10 dB.…”
Section: Rhis Designmentioning
confidence: 99%
“…The optimal resistor value depends on both angle of incidence and wave polarization w = 9.7 mm g=0.25 mm h = 2.36 mm r = 2. [15]. This structure is characterized by the absorption band that we defined by |U| \ -10 dB.…”
Section: Rhis Designmentioning
confidence: 99%
“…The absorption peak moved to higher frequency obviously with the value of FSS period increased. The reason might be that the resonant frequency of the FSS is determined by the volume fraction of aluminum film mostly, which is similar to the RL results of the absorber incorporated with other FSS structure [17][18][19][20][21][22][23]. For the sample CCNT4, circular aluminum patches FSS with unit 2r = 1.4 mm and c = 9.2 mm were chosen to design the absorber, and the insert in Fig.…”
Section: Microwave Absorption Of the Ccto And Mwcnt Composites With Fssmentioning
confidence: 99%
“…As mentioned above, compared with the single absorber (MWCNTs or CCTO particles)-filled composites and MWCNT-, and CCTO particle-filled epoxy composites are good candidates for fabricating microwave absorbers with high absorption, due to the significant potential to obtain suitable complex permittivity and dielectric loss. In addition, it has also been indicated that the design of microwave absorbers with frequency-selective surface (FSS) can be used to improve their microwave absorption [17][18][19][20][21][22][23][24]. Using a FSS and RAMs design, microwave absorption can be enhanced by optimizing the impedance matching and attenuation characteristic of the absorber, adjusting the pattern, square resistance of the FSS.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a seemingly contradictory problem when trying to minimize the reflection coefficient for both polarizations simultaneously. To tackle this problem, a practical solution proposed in [14] is to consider an FSS with different dimensions along x and y directions, each one dedicated to one polarization. This leads to a rectangular unit cell, as shown in Figure 2b.…”
Section: Description Of the Absorbersmentioning
confidence: 99%
“…In a previous study by the authors, two metamaterial absorbers for space applications based on resistive high impedance surface solution were proposed for the TT&C (Telemetry, Tracking and Control) S-band [2 GHz,2.3 GHz], optimized respectively for normal and oblique (60 • from normal direction) for both TE (Transverse Electric) and TM (Transverse Magnetic) polarization [13,14] with experimental validation. These two metamaterial absorbers were designed for a specific and limited range of angle of incidence which was well adapted to the case of an antenna being positioned far away from the structure.…”
Section: Introductionmentioning
confidence: 99%